Enhanced adoptive transfer of immunity to Listeria monocytogenes after in vitro culture of murine spleen cells with concanavalin A. - Barry, R A (1982)
In vitro incubation of spleen cells with T-cell mitogens has been shown to augment cytotoxic and cytolytic T-cell function. The plant lectins Concanavalin A and phytohemagglutinin were employed in a similar fashion to investigate their abilities to enhance cell-mediated immunity to the microbial pathogen Listeria monocytogenes. Spleen cells from immune mice were incubated in vitro with Concanavalin A or phytohemagglutinin before passive transfer into normal recipients. Results indicated a 10- to 100-fold enhancement in the ability of these cells stimulated in vitro to transfer antilisterial resistance, as assayed by changes in 50% lethal dose values and enumeration of splenic bacterial proliferation.